(untitled) (Research, Society and Development, 2021)
The presence of people who inhabit the streets of large Brazilian cities expresses a phenomenon that is frequently expanding. Thus, the present study aimed to analyze the mental health conditions of homeless adults in the city of Feira de Santana - Bahia. For that, it was necessary the voluntary participation of eight adults, both genders, aged between 25 and 32 years old, and who had the streets as living environments and socialization context. As instruments, semi-structured interviews were used with a pre-established script. The adults participating in the study presented important data about the mental health conditions related to the environment they live or attend, reporting the risks and social vulnerabilities that permeate in their presence. In addition, they reported on their choices and conditions of factors that led or allowed them to be on the streets of the city. However, homeless adults are a public that has a high level of vulnerability due to the circumstances in which they find themselves.